2018
DOI: 10.1083/jcb.201802095
|View full text |Cite
|
Sign up to set email alerts
|

The cell biology of systemic insulin function

Abstract: Insulin is the paramount anabolic hormone, promoting carbon energy deposition in the body. Its synthesis, quality control, delivery, and action are exquisitely regulated by highly orchestrated intracellular mechanisms in different organs or "stations" of its bodily journey. In this Beyond the Cell review, we focus on these five stages of the journey of insulin through the body and the captivating cell biology that underlies the interaction of insulin with each organ. We first analyze insulin's biosynthesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
262
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(292 citation statements)
references
References 224 publications
(266 reference statements)
5
262
0
5
Order By: Relevance
“…Nevertheless, Sassek et al [28] reported that insulin secretion from cultured cells and isolated islets was reduced by SPX, and insulin secretion decreased after injection with SPX in obese rats. These results suggest that SPX may suppress over-secretion of insulin, which in turn may contribute to the improvement of insulin sensitivity [29].…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, Sassek et al [28] reported that insulin secretion from cultured cells and isolated islets was reduced by SPX, and insulin secretion decreased after injection with SPX in obese rats. These results suggest that SPX may suppress over-secretion of insulin, which in turn may contribute to the improvement of insulin sensitivity [29].…”
Section: Discussionmentioning
confidence: 85%
“…Arp2/3 is thought to act downstream of Rac1 (Chauhan, Lou, Zheng, & Lang, ; Ridley, ). Insulin‐induced activation of Rac1 in muscle cells was found to result in dynamic actin remodeling with the formation of cortical F‐actin structures that was mediated by Arp2/3‐dependent branching of F‐actin and led to the translocation of the glucose transporter GLUT4 (encoded by Slc2a4 ) from the cytoplasm to the plasma membrane (Chiu, Patel, Shaw, Bamburg, & Klip, ; Tokarz, MacDonald, & Klip, ). Arp2/3 has been also found to regulate adipocyte differentiation through control of the formation of cortical F‐actin structures in 3T3‐L1 preadipocytes (Yang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, downstream of PI3K, and in parallel with Akt activation, PI3K also phosphorylates/activates the Rho‐family GTPase Rac1, which promotes GLUT4 translocation by initiating cortical actin filaments remodelling (Tokarz et al . ). Rac1 plays an important role in the reorganization of the actin cytoskeleton and is also essential for insulin‐stimulated glucose transport.…”
mentioning
confidence: 97%
“…This reorganization of the cytoskeleton allows for the translocation of GLUT4 transporters to the plasma membrane, which increases glucose uptake into the cell (Tokarz et al . ). However, it is important to state, that this has not been shown in vivo (Madsen et al .…”
mentioning
confidence: 97%
See 1 more Smart Citation